Pengenalan Metode FAST dalam Mengembangkan SIM untuk Meningkatkan Pelayanan Hotel - Fetty Ade Putri; Rida Utami; Lubis, Larassati Oktaviani (LPPM Universitas Potensi Utama, 2022)
Management Information System or abbreviated as SIM is one of the information systems currently needed by many business organizations, because the need for information in this increasingly modern era is absolute. In order to develop MIS, the FAST (Framework for the Application of System Thinking) method can be applied. FAST is a flexible method because it can be combined with other techniques and methods, and can help develop systems quickly. In applying the FAST method there are 8 (eight) stages, namely, (1) Scope Definition, (2) Problem Analysis, (3) Requirements Analysis, (4) Logical Design, (5) Decision Analysis, (6) Physical Design, ( 7) Construction and Testing, and (8) Installation and Delivery. The result of community service is the increasing understanding of both management and hotel staff regarding SIMs, the FAST method, and the application of the FAST method in order to develop a SIM to improve services to visitors